Responses of Photosynthetic and Defence Systems to High Temperature Stress in Quercus suber L Seedlings Grown under Elevated CO2 (Plant biology (Stuttgart, Germany), 2008)
Growth in elevated CO2 led to an increase in biomass production per plant as a result of enhanced carbon uptake and lower rates of respiration, compared to ambient C02-grown plants. No down-regulation of photosynthesis was found after six months of growth under elevated CO2. Photosynthetic rates at 15°C or 35°C were also higher in elevated than in ambient C02-grown plants, when measured at their respective CO2 growth condition. Stomata of elevated C02-grown plants were less responsive to temperature as compared to ambient CO2 plants. The after effect of a heat-shock treatment (4 h at 45°C in a chamber with 80% of relative humidity and 800—1000 tmol rn2 photon flux density) on Amax was less in elevated than in ambient C02-grown plants. At the photochemical level, the negative effect of the heat-shock treatment was slightly more pronounced in ambient than in elevated CO2-grown plants. A greater tolerance to oxidative stress caused by high temperatures in elevated C02-grown plants, in comparison to ambient CO2 plants, is suggested by the increase in superoxide dismutase activity, after 1 h at 45°C, as well as its relatively high activity after 2 and 4 h of the heat shock in the elevated C02-grown plants in contrast with the decrease to residual levels of superoxide dismutase activity in ambient C02-grown plants immediately after 1 h at 45°C. The observed increase in catalase after 1 h at 45°C in both ambient and elevated C02-grown plants, can be ascribed to the higher rates of photorespiration and respiration under this high temperature.